Development and Characterization of Hybrid Nanocomposites for Biosensing Applications (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The synthesis and characterization of hybrid nanocomposites have emerged as a pivotal area of research in the development of advanced biosensing technologies. Hybrid nanocomposites, which integrate organic and inorganic materials at the nanoscale, exhibit unique properties that enhance sensitivity, specificity, and stability in biosensing applications. This study focuses on the design, synthesis, and detailed characterization of hybrid nanocomposites tailored for biosensing. Utilizing a combination of chemical and physical methods, various hybrid nanocomposites were synthesized, incorporating materials such as metal nanoparticles, carbon nanotubes, and polymer matrices. Advanced characterization techniques, including transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier-transform infrared spectroscopy (FTIR), were employed to elucidate the structural and compositional attributes of the synthesized nanocomposites. The electrochemical and optical properties of the hybrid nanocomposites were thoroughly investigated to assess their biosensing performance. The results demonstrated that the hybrid nanocomposites possess enhanced catalytic activity, improved electron transfer rates, and increased surface area, which are critical for high-performance biosensors. The functionalization of these nanocomposites with specific bioreceptors, such as enzymes, antibodies, and nucleic acids, was optimized to achieve selective and sensitive detection of various biological analytes.